2011
DOI: 10.1186/1617-9625-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco retailer density surrounding schools and youth smoking behaviour: a multi-level analysis

Abstract: BackgroundYouth smoking prevention should be a public health priority. It is not only vital to prevent youth from smoking but also to prevent non-smoking youth from becoming susceptible to smoking. Past research has examined factors associated with youth's susceptibility to become a future smoker, but research has yet to examine tobacco retailer density and susceptibility to smoking among never smokers. The objectives of this study are to examine how tobacco retailer density surrounding schools and social smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 28 publications
7
84
1
3
Order By: Relevance
“…This finding contradicts the study by Wilkinson et al (2008), Ertas (2007), Chan and Leatherdale (2011) and Huang et al (2012) that says respondents with a brother or parent who smoke were more likely to be susceptible to smoking (OR 2.65; 95%CI 1.48-4.76; 1.17; 95%CI 1.04-1.31; 1.35; 95%CI 1.16-1.58); this could be due to the older age of respondents in the current study compared to the other studies which show that parents' influence would gradually decline as their children grew older because parental control naturally slips with the increasing age of their offspring (Baumrind, 1991). Older adolescents were more likely to obtain autonomy from the family as they seek self-identity through increasing time spent on school activities and also becoming less involved with their parents.…”
Section: Discussioncontrasting
confidence: 70%
“…This finding contradicts the study by Wilkinson et al (2008), Ertas (2007), Chan and Leatherdale (2011) and Huang et al (2012) that says respondents with a brother or parent who smoke were more likely to be susceptible to smoking (OR 2.65; 95%CI 1.48-4.76; 1.17; 95%CI 1.04-1.31; 1.35; 95%CI 1.16-1.58); this could be due to the older age of respondents in the current study compared to the other studies which show that parents' influence would gradually decline as their children grew older because parental control naturally slips with the increasing age of their offspring (Baumrind, 1991). Older adolescents were more likely to obtain autonomy from the family as they seek self-identity through increasing time spent on school activities and also becoming less involved with their parents.…”
Section: Discussioncontrasting
confidence: 70%
“…Results of these studies are mixed. Some studies have found no or small effects (Leatherdale & Strath, 2007; Lovato et al, 2007;McCarthy et al, 2009;Pokorny et al, 2003) and others have shown stronger associations with youth smoking (Chan & Leatherdale, 2011;Henriksen et al, 2008; Lipperman-Kreda et al, 2014b;Novak et al, 2006;West et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A modest body of cross-sectional research has investigated the association between exposure to tobacco outlets around schools or residential areas and tobacco use among youths (Chan & Leatherdale, 2011;Henriksen et al, 2008;Leatherdale & Strath, 2007;LippermanKreda et al, 2014b;Lovato, Hsu, Sabiston, Hadd, & Nykiforuk, 2007;McCarthy et al, 2009;Novak, Reardon, Raudenbush, & Buka, 2006;Pokorny, Jason, & Schoeny, 2003;West et al, 2010). Results of these studies are mixed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations